Formação continuada e desenvolvimento profissional docente nas escolas de ensino integral de São Paulo - Silva, Wellynton Rodrigues da (2019)
São Paulo state government instituted, with the Supplementary Law n. 1.164, of January 4, 2012, the Full-time Education Program, increasing teachers’ and students’ work and study hours in 16 pilot schools in São Paulo, proposing changes in the curriculum, methodologies and forms of service and administration, as well as bringing as premise the investment in actions of continuing education in order to fulfill the needs of those teachers and schools. We propose in this investigation to identify and describe aspects of those continuing education actions offered in the schools of this program, analyzing whether they enable those teachers to the claimed self-formation, providing them autonomy to plan and manage their own formation project. It is an analytical-descriptive study of the teachers’ continuing formation actions of a Secondary Education School, which participated in the Full-time Education Program of São Paulo, situated in the capital of the State. Such school was chosen because it presented the lowest professional rotativity among the 16 schools which have initially been part of the Program in the state of São Paulo, since 2012. The qualitative research was accomplished by means of documental analysis (specific legislation and documents produced to the school by the administrative boards and by the school in its daily routine); questionnaires and interviews with 05 teachers, 02 coordinators and 01 school principal, observation of the teachers’ and school administrative staff’s work routine and environment. Theoretical support to the investigation was provided by authors, such as: Marcelo, Tardif, Marin, Candau, Hargreaves and Giovanni (for the definition of teacher continuing education, professional development and teachers’ knowledge); García Del Dujo and Rodriguez (concerning the concept of self-formation); Barroso (conceptualizing the formation centered on the school); and Viñao Frago (concerning the concept of administrators’ and teachers’ school culture). Data obtained confirmed the hypothesis that the teachers’ continuing education, assured by the Law and organized by means of Resolutions, is founded in top-down elaborated legislation, without considering the needs of the school as well as the teachers. Its principles are based on hardly effective traditional models of continuing education, whose approach prioritizes the teachers’ instrumentalization to apply and reproduce the curriculum, standardizing routines and practices. The authoritarian way the richest Brazilian state – São Paulo – determined to manage its educational system has brought consequences to all the school agents, specially to the teachers, who are the final responsible for the implementation of the changes proposed, demonstrating centralism in the decisions and concern with the curricula standardization, without taking into consideration the school culture, the teachers’ culture and their knowledge